A Case of Dissecting Cellulitis which Was Initially Suspected to Be a Trichilemmal Cyst. Issue 7 (6th July 2021) - Masuda, Yashumitsu; Kuwahara, Masamitsu; Ando, Junji; Miyata, Riyo; Harada, Masayuki; Takeuchi, Mika; Kanagawa, Saori; Mashiba, Kumi; Yurugi, Satoshi
Abstract : Summary: We treat infected cysts on a daily basis, but it is difficult to diagnose similar lesions produced by inflammatory conditions that are not primarily caused by bacteria. Dissecting cellulitis of the scalp (DCS) is a chronic inflammatory disease that results in disfiguring, painful, and purulent lesions. It often takes a long time to diagnose. The pathophysiology of DCS remains unclear. Various treatments for DCS have been proposed, depending on the severity of the disease. However, none of these treatments are clearly superior to the others. If DCS spreads to the entire occipital region, aggressive surgical treatment may be beneficial in terms of the patient's quality of life. However, surgical interventions, such as drainage, are not effective at preventing the progression of the disease. Herein, we report the case of a young female patient who developed a cyst in the occipital region. We initially suspected that the lesion was a normal infected trichilemmal cyst. However, DCS was subsequently suspected because the lesion exhibited an unusual course after drainage and debridement. We consider that we made a diagnosis relatively early, but if we had sufficient knowledge about DCS we could have made a diagnosis even earlier by performing debridement sooner. Minocycline was administered for 5 months, which caused the lesion to disappear. After 2 years, no recurrence had been observed.